Jackfruit Starch Based Blends with Polyvinylpyrrolidone: Preparation, Structural Characterization, and Biodegradable Properties. Issue 1 (19th June 2022) - Pokhrel, Shanta; Limbu, Shova Kumari; Subedi, Subhangi
Abstract: Starch is extracted from the seeds of ripen jackfruit ( Artocarpus heterophyllus ) cultivated in Nepal by treating with distilled water and alkali solution. The properties of extracted starch are evaluated by measuring ash content, moisture content, and amylose content. A series of starch‐based biodegradable blends with polyvinylpyrrolidone (PVP) are prepared through solution casting method and their biodegradable properties are studied. The blend is characterized by thickness measurement, water solubility test, Fourier transform infrared spectroscopy (FTIR), optical microscopy, and biodegradability test. The thickness measurement shows the linear increase in thickness of the blend with the addition of starch. The water solubility test reveals the higher solubility of PVP in water than that of the starch. FTIR spectra of PVP/thermoplastic starch (PVP/TPS) blends exhibit the existence of relevant functional groups of both starch and PVP, the peaks shifting, and the change in nature of the peaks after degradation. Optical microscopy reveals the nonuniform dispersion of starch particles in the PVP matrix and the appearance of holes and fractures in composite subjected to compost soil for degradation. The biodegradability study proves that the loading of starch to PVP accelerates the degradation process.